Thermal Stability of the Eutectic Composition in NaCl-CaCl2-MgCl2 Ternary System Used for Thermal Energy Storage Applications. (May 2017) - Du, Lichan; Tian, Heqing; Wang, Weilong; Ding, Jing; Wei, Xiaolan; Song, Ming
Abstract: The ternary eutectic chloride salt (NaCl-CaCl2 -MgCl2 ) was designed and prepared for thermal energy storage over 550 °C in a concentration solar power system. The melting temperature and fusion enthalpy of the eutectic salt were measured experimentally using the Differential Scanning Calorimeter (DSC) technique which were determined to be 420.83 °C and 201.50 J/g, respectively. The thermal stability including the short-term and the long-term thermal stability of the ternary system was investigated by the Thermo-gravimetric Analyzer (TGA) technique and the DSC technique. The thermal properties of the eutectic mixture kept stable during the short-term thermal cycling test. The weight loss of the eutectic salt was less than 5%, and the melting temperature and fusion enthalpy changed slightly as the temperature increased below 650 °C in the long-term isothermal stability study. The thermal stability test revealed that the ternary eutectic system demonstrated excellent thermal stability below 650 °C which was taken as the upper limit temperature of the ternary system. The eutectic composition was characterized by the X-Ray Diffraction (XRD) technique before and after thermal treatment to provide preliminary analysis on the mechanism of thermal instability. The results suggested that the ternary eutectic chloride salt was a potential candidate for applying in high-temperature thermal energy storage.